FACIES ANALYSIS, PALAEOENVIRONMENTAL RECONSTRUCTION, AND BIOSTRATIGRAPHY OF THE "PESCIARA DI BOLCA" (VERONA, NORTHERN ITALY): AN EARLY EOCENE FOSSIL-LAGERSTäTTE - Papazzoni C.A.; Trevisani E. (My University, 2006)
The world-famous "Pesciara di Bolca" Fossil-Lagerstätte has been examined in its palaeontological and sedimentological aspects. A re-examination of the co-occurring age-diagnostic larger foraminifers (Alveolina and Nummulites) indicates a SBZ 11 (late Ypresian) age. Sedimentological characters allowed us to distinguish between autochthonous micritic limestones and allochthonous biocalcarenites-biocalcirudites; the latter are the product of penecontemporaneous transport from nearby areas. The depositional model here proposed involves a basin with restricted circulation and a prevailing micrite sedimentation. This basin was affected by relative sea-level oscillations and coarser grained storm-induced deposition. The palaeoenvironmental reconstruction suggests neighbouring emerged land and very shallow sea bottoms inhabited by large foraminifers such as Alveolina and Nummulites. As yet, it is unclear whether a true coral reef was present nearby. The bottom on which the Pesciara deposits accumulated is interpreted as poorly oxygenated, possibly with stromatolite-like bacterial mats, thus allowing the exceptional preservation of the fish and plants. © 2006 Elsevier B.V. All rights reserved.
Keywords: ALVEOLINA; BIOSTRATIGRAPHY; EARLY EOCENE; ITALY; PALAEOENVIRONMENT; SEDIMENTOLOGY; Ypresian; Cenozoic::Paleogene::Eocene::Ypresian; Кайнозой::Палеоген::Эоцен::Ипрский